The Road to Upward Mobility: Urbanity and the Creation of a New Middle Class in Postwar West Germany. (May 2014) - Staub, Alexandra
In the years after World War II, West Germany (after 1949 the Federal Republic of Germany, or FRG) experienced a severe housing shortage coupled with a demand—unambiguously conveyed by the occupying powers—to "modernize" and socially restructure. With war-torn cities needing extensive repair, politicians and planners made choices that affected not only the physical but also the social landscape, with the federal government ultimately using urban policy in an attempt to redefine identity and help shape a new middle class. This article traces this process by examining three postwar policy directions—suburbanization, urban high-rise housing, and automobile ownership—both as an economic driver and as a first toehold on the ladder to upward mobility. I argue that not only did these policy foci fundamentally change the FRG's urban landscape, their physical manifestations became central to the nation's often-acrimonious debate over societal modernization.